Short-interfering RNAs as antivirals against rabies - Brandão,Paulo Eduardo (2007)
This study aimed to test in vitro a RNA-interference based antiviral approach for rabies with short-interfering RNAs (siRNAs) against rabies virus nucleoprotein mRNA. BHK-21 cells were infected with serial dilutions of PV rabies virus strain and transfected with a pool of three siRNAs. Direct immunofluorescence staining showed a 5-time decrease in virus titer when compared to a non-treated plate, showing a promising new approach to the development of antivirals for rabies treatment.